SAT0360 Low bone mass is associated with carotid intima-media thickness and atherosclerotic plaque in postmenopausal women referred for osteoporosis screening. (23rd January 2014) - Muntean, L.M.; Simon, S.P.; Albu, A.; Poanta, L.; Rednic, S.; Fodor, D.
Abstract : Background: Low bone mineral density (BMD) has been associated with cardiovascular diseases (CVD) and markers of subclinical atherosclerosis, suggesting a shared pathophysiology. Objectives: The objective of this study was to evaluate the relationships between bone mineral density (BMD) and intima-media thickness (IMT) of the common carotid artery and carotid atherosclerotic plaque in a cohort of postmenopausal women. Methods: In this cross-sectional study were consecutively enrolled 184 postmenopausal women referred for osteoporosis screening by dual energy X-ray absorptiometry (DXA) scanning of the lumbar spine and hip. Mean common carotid IMT, as a marker of subclinical atherosclerosis, and the presence of atherosclerotic plaques were assessed by ultrasonography. Results: In patients with total hip osteoporosis, mean IMT was significantly higher than in patients with osteopenia or normal BMD (both p<0.05). There was no statistically significant difference in the mean values of IMT across the spine bone status (p=0.07). Sixty-three percent of patients with osteoporosis at the femoral neck had carotid artery plaque at one or more sites compared with 38% for women with normal BMD (p=0.04). There was no statistically significant trend in the proportion of atherosclerotic plaques across the spine and total hip bone status groups. A significant positive correlation was observed between mean IMT and BMD Z-score at the lumbar spine (rho =0.19, p=0.008). In regression analysis, femoral neck BMD, but not total hip or lumbar spine BMD, was negatively associated with mean carotid IMT (p=0.04). Conclusions: Low bone mass in postmenopausal women is associated with increased carotid IMT and atherosclerotic plaque. Our results provide further evidence for a link between BMD and the risk of atherosclerotic cardiovascular diseases. References: Den Uyl D, Nurmohamed MT, van Tuyl LH et al. (Sub)clinical cardiovascular disease is associated with increased bone loss and fracture risk; a systematic review of the association between cardiovascular disease and osteoporosis. Arthritis Res Ther 2011;13(1):R5. Sumino H, Ichikawa S, Kasama S, et al. Relationship between carotid atherosclerosis and lumbar spine bone mineral density in postmenopausal women. Hypertens Res 2008; 31:1191-97. Jorgensen L, Joakimsen O, Rosvold Berntsen GK, et al. Low bone mineral density is related to echogenic carotid artery plaques: a population-based study. Am J Epidemiol 2004;160:549-56. Disclosure of Interest: None Declared